Valuation Model for the Merger & Acquisition of PT Bank Harda Internasional Tbk (BBHI) Shares by PT Bank Mega Tbk (MEGA) - Nugroho, Yusuf Wahyu; Haekal, Jerry (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The digital sector's growth, particularly during the pandemic, prompted companies' digital transformations. Fintech's rise in finance drove major banks to focus on digital banking, leading to the increased popularity of mergers and acquisitions (M&A) for expansion. This study aims to establish a suitable transaction structure and price for PT Bank Harda International Tbk (BBHI) acquisition by PT Bank Mega (MEGA). Comparing this with MEGA's 2021 strategy, the valuation of BBHI and MEGA assesses merger prospects. The research uses quantitative and descriptive analysis of BBHI and MEGA's finances, employing Discounted Free Cash Flow, Liquidation and Accounting Valuation, and Relative Valuation. Synergy's role in enhancing merger value is considered. Results project growth in key metrics for both companies over five years, with the merger significantly boosting equity, market capitalization, and enterprise value. A 17.6% internal rate of return (IRR) makes the acquisition appealing. BBHI's equity value per share (Rp.731) compared to prior transaction prices (Rp.160) indicates undervaluation but the positive market response is reflected in the post-acquisition share price rise. The analysis underscores considerable post-merger value enhancement, favoring MEGA's market capitalization and enterprise value, benefiting both parties and supporting BBHI's merger with PT Bank Mega, Tbk under PT Mega Corpora. Keywords: Merger, Acquisition, FCF, IRR, Bank.